2012
DOI: 10.5539/jas.v4n9p187
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Organic and Inorganic Seed Treatments on the Viability and Vigour of Sesame Seeds in Storage

Abstract: This study was undertaken to determine the storability of pre-treated sesame seeds and to compare the effects of inorganic and organic seed treatments on the viability and vigour of sesame seeds during storage. Two hundred grammes of sesame seeds were treated separately with recommended dosages of Neem leaf powder (NLP), Dress force powder (DFP), Dry pepper powder (DPP) and untreated seeds being the control; each treatment placed in air-tight container and stored in a wooden cabinet at average ambient conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 6 publications
(6 reference statements)
3
15
0
2
Order By: Relevance
“…Suas sementes contêm cerca de 50 a 60% do seu peso seco, sendo ricas em vitamina e sais minerais (OBIAJUNWA et al, 2005). A demanda por sementes de gergelim e seus produtos está crescendo a níveis nacional e internacional (OYEKALE et al, 2012). Ela é preferencialmente consumida em comidas orientais (SUH et al, 2003), sendo consumida também pelas suas qualidades medicinais (KHAZAEI e MOHAMMADI, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Suas sementes contêm cerca de 50 a 60% do seu peso seco, sendo ricas em vitamina e sais minerais (OBIAJUNWA et al, 2005). A demanda por sementes de gergelim e seus produtos está crescendo a níveis nacional e internacional (OYEKALE et al, 2012). Ela é preferencialmente consumida em comidas orientais (SUH et al, 2003), sendo consumida também pelas suas qualidades medicinais (KHAZAEI e MOHAMMADI, 2009).…”
Section: Introductionunclassified
“…Essa avaliação é importante, visto que a deterioração da semente inicia-se imediatamente após a cultura ter atingido o estágio de maturidade fisiológica (OYEKALE et al, 2012).…”
Section: Introductionunclassified
“…The storability of seeds is also influenced by the type of packaging material. Seeds stored in moisture-proved sealed containers provide suitable environment for storage, offer protection against contamination and also acts as a barrier against the escape of seed treatment chemicals than in moisture pervious containers higher viability and vigour was retained for longer period in moisture-proof containers followed by moisture resistant and impervious containers respectively (Oyekale et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in order to prevent the quantitative and qualitative losses due to several biotic and abiotic factors during storage, several methods are being adopted such as seed treatment with suitable chemicals or plant products, as well as seed storage in safe containers. Oyekale et al (2012) reported that seed deterioration during storage was due to the damage in cell membrane and other chemical changes in the seed system such as the protein and nucleic acid accumulation. Such degenerative changes result in complete disorganization of membranes and cell organelles and ultimately causing death of the seed and loss of viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation